Zwei koptische grammatische Morpheme bislang ungeklärten Ursprungs - Peust, Carsten (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
This paper discusses two Coptic morphemes whose etymology has remained obscure to this day, namely the n -prefix of the so-called adjective verbs such as ⲛ-ⲁⲛⲟⲩ= „is good“, as well as the particle ⲡⲉ that often accompanies the preterite converter. It is suggested that both of them came into existence by a false segmentation of contexts in which their predecessors typically used to occur.